Stamp impressions from ancient Artashat in Armenia - Lichtenberger, Achim; Schreiber, Torben; Ting, Carmen; Zardaryan, Mkrtich H. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
During the 2022 excavations in Artashat (ancient Artaxata) in Armenia, an assemblage of pre-Hellenistic stamped pottery sherds was found. The stamps are of a new type and seem to relate to the local administration. In the paper a discussion of the iconography, use and petrography as well as the date of the new material is presented.